Analisis Pengaruh Faktor Bauran Pemasaran Terhadap Keputusan Pembelian Ulang Pada Produk Susu Kalimilk Di Yogyakarta - Novi Afriyani; Minar Ferichani; Mei Tri Sundari (Universitas Sebelas Maret, 2018)
The purpose of this research was to know factors that considered by consumer and reviewing dominant variables affecting consumers consideration toward repeat purchase decision on Kalimilk product in Yogyakarta. The basic method of this research is analytical description. Location methods performed by purposive sampling method. The location was used as a place of research is the main store of Kalimilk in Kaliurang Km 4.5 Yogyakarta. Method of sampling done by purposive sampling. The total sample set was as much as 96 respondents. The data source is primary and secondary data. Data analysis used in this research is factor analysis. The results showed that from the 14 variables that were analyzed, it can be simplified into 13 variables and is included in the three core factors. Based on the priority factor, there are, the factor of suitability of products that have percentage of variance 49.023%, place factors that have a variance percentage value of 12.450%, and promotional factors that have a variance percentage value of 8.585%. While most dominant variable considered by consumers in the purchase decision of dairy products Kalimilk from each of the core factors that form the variable affordability of product form suitability factors, variable comfort of a place factor, and a variable bonus of promotion factor. The dominant variable for all variables are researched based on the loading factor value of all the variables is a variable bonus to the value of factor loading 0.876, affordability with a value of factor loading 0.860, and variable social media with a value of factor loading of 0.858.